# How do you solve #2( z - 4) + 3= 5- ( z + 1)#?

##### 2 Answers

Apr 22, 2018

#### Explanation:

Apr 22, 2018

#### Explanation:

#"distribute parenthesis on both sides of the equation"#

#2z-8+3=5-z-1larrcolor(blue)"simplify both sides"#

#rArr2z-5=-z+4#

#"add z from both sides"#

#2z+z-5=cancel(-z)cancel(+z)+4#

#rArr3z-5=4#

#"add 5 to both sides"#

#3zcancel(-5)cancel(+5)=4+5#

#rArr3z=9#

#"divide both sides by 3"#

#(cancel(3) z)/cancel(3)=9/3#

#rArrz=3#

#color(blue)"As a check"# Substitute this value into the equation and if both sides are equal then it is the solution.

#"left "=2(-1)+3=-2+3=1#

#"right "=5-(4)=1#

#rArrz=3" is the solution"#